L-Arginine effectively alleviates doxorubicin-induced cardiac dysfunction by inhibiting myocardial fibrosis - Mo-li Zhu; Rui Hao; Meng-yao Zhao; Pei-yao Liu; Hong-dou Zhang; Peng Li; Ya-ling Yin; Hui-jun Liu; Guang-qiu Ren; Jie Zhang; Jing Yang (Molecular Biology Reports, 2026)

Carbon dot-based catalytic materials: From photo/electrocatalysis to nanozyme activity - Pei-De Zhu; Chang Liu; Hui Wang; Rong-Yu Yao; Ling-Rui Sun; Xin-Ru Xu; Jing-Wen Jiang; Ying-Sheng Xu; Kun-Peng Lin; Jia-Xing Wu (Journal of Environmental Chemical Engineering, 2026)

Copper and sulfonamide co-remediation by Pleurotus ostreatus GEMB-PO1: Efficiency, mechanisms, and enhancement strategies - Xuan Gao; Ling Feng; Nasi Zhang; Yumei Chen; Yonghua Zhu; Rui Zhuo (Journal of Environmental Chemical Engineering, 2026)

A lyophilized RPA–CRISPR/Cas13d one-pot platform for rapid detection of porcine circovirus type 3 - Li-Na Shao; Zheng-Luo; Bao-Ling Liu; Tong-Xu; Yuan-Meng Wang; Jia-Qi Duan; Lei-Zhao; You-You Li; Yang-Ming Dai; Qin-Rui Jia; Le-Yi Zhang; Ling-Zhu; et al. (Analytica Chimica Acta, 2026)

Accurate counting of small and dense Chinese cherry in natural orchard via fruit-oriented perception and sharpening network - Shizhuang Weng; Rui Deng; Jian Xu; Qi Wu; Shenao Sun; Yudi Chen; Huiwen Yang; Nina Zhu; Jialing Chen; Ling Zheng; Zede Zhu (Computers and Electronics in Agriculture, 2026)

Metabolic complementarity in LAB-yeast co-fermentation associates with enhanced ester aroma in cream cheese - Beibei Duan; Yueyue Zhou; Siyu Wang; Ling Yan; Yujie Lin; linze Li; Bin Xue; Rui Huang; Yipan Zhang; Yue Cui; Nan Wu; Xiangting Kong; et al. (Food Research International, 2026)

Serum exosomes protect heat-stressed mouse 2-cell embryos: Enhanced antioxidant defense and base excision repair of oxidative DNA damage - Hong-Chuan Zhang; Si-Jing Qu; Xin-Lei Yan; Rui-Cong Wang; Shi-Yong Zhu; Rong-Feng Cao; Kai-Qiang Fu; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Exposure to high ambient temperature during pre-implantation impairs embryo transport and development in the oviduct: Potential association with ANO1 downregulation - Hong-Chuan Zhang; Rui-Cong Wang; Shi-Yong Zhu; En-Yan Wang; Yu-Feng Huang; Rong-Feng Cao; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Environmental cadmium drives placental senescence and fetal growth restriction via activating CLPP-dependent mitochondrial stress - Rui Pan; Jin Zhang; Lan-Lan Wu; Cheng-Fang Sun; Xin-Xin Zhang; Yu-Xi Wu; Xu-Ai Yin; Ye-Xin Luo; Si-Ting Liu; Zi-Jian Bao; Wei Chang; Ling-Li Zhao; et al. (Journal of Hazardous Materials, 2026)

Robust under-canopy navigation path extraction for collaborative harvesting robots using semi-supervised UniMatch V2 segmentation enhanced by edge-contour keypoint clustering - Rui Su; Cheng Liu; Zhentao Zhu; Ling Wang; Xu Mao; Lei Gao; Du Chen (Computers and Electronics in Agriculture, 2026)

Multi-source remote sensing unveils hydrological dynamics and drought escalation in Central Asia’s arid regions - Yuhao Wang; Zhijie Zheng; Guofeng Zhu; Enwei Huang; Gaojia Meng; Siyu Lu; Dongdong Qiu; Longhu Chen; Rui Li; Yinying Jiao; Ling Zhao; Xiaoyu Qi; et al. (Journal of Geographical Sciences, 2026)

Cloning, heterologous expression, and characterization of a metagenome-derived GH10 xylanase with salt and alkali tolerance from Xinjiang saline-alkali soil - Jing Gao; Hua-Lin Li; Mao-Song Li; Zong-Jin Shao; Zheng-Feng Yang; Chan-Jin Li; Zhi-Xin Zhang; Dan Zhu; Zhi-Hua Lv; Rong-Huan Song; Jian-Ling Li; Wei Hu; et al. (Antonie van Leeuwenhoek, 2026)

Geospatial machine learning for benzene estimation in an environmentally disadvantaged area: Snapshot air quality assessment of Joppa community, Dallas, Texas - Aji Kusumaning Asri; Galen D. Newman; Zhihan Tao; Rui Zhu; Hsiu-Ling Chen; Shih-Chun Candice Lung; Chih-Da Wu (Journal of Cleaner Production, 2026)

Paper garland-inspired 2D single-phase spiral folded-rod elastic metamaterial for extremely low-frequency vibration isolation - Kai Miao; Leilei Wang; Wencheng Yin; Rui Zhang; Shuyuan Liu; Facheng Song; Jian Zhu; Lingling Wu; Jianhui Liang; Dichen Li; Ling Wang (Engineering Structures, 2026)

Triple-synergistic nanotherapeutics for acute and chronic colitis management via programmable multidimensional modulation - Penghui Wang; Yue Zhao; Ning Tian; Xiangling Liu; Tenghui Tian; Difu Zhu; Fangbing Liu; Hengyan Liu; Ling Li; Zhiyu Ren; Deok Chun Yang; Lei Zhao; et al. (Chemical Engineering Journal, 2026)

Simultaneous remediation of heavy metals in mining soil using nZVI-supported attapulgite - Jun Ren; Caili Tong; Hanru Ren; Ming Gao; Gui Ma; Yunmeng Li; Rui Zhu; Xuri Mu; Chun Yang; Ling Tao (Environmental Geochemistry and Health, 2026)

High-fidelity removal of strawberry leaf occlusion via outline-texture improvement network - Ling Zheng; Huiwen Yang; Yudi Chen; Shenao Sun; Hui Zhang; Rui Deng; Nina Zhu; Jialing Chen; Shizhuang Weng (Computers and Electronics in Agriculture, 2026)

New endiandric acid analogues from Cryptocarya hainanensis - Yu Liu; Lei Miao; Qian He; Zhu-Ling Shao; Chuan-Rui Zhang (Natural Product Research, 2026)

Early-life exposure to polystyrene nanoplastics at ambient doses induces neurotoxicity via mTOR-mediated autophagy-lysosomal dysfunction and proteostasis imbalance - Ge Yang; Yang Peng; Jinghan Li; Shuiqing Yang; Min Li; Xinyue Zheng; Xinyue Chen; Jian Wan; Zhihong Zhu; Ling Zhang; Rui Li (Journal of Hazardous Materials, 2026)

Enhanced degradation of microplastics by laccase under ambient conditions: Analysis of underlying molecular mechanisms - Rui Ding; Linhan Xu; Xiaoling Shan; Xinran Qiu; Ling Ding; Bin Zhang; Xujun Liang; Lingyan Zhu; Xuetao Guo (Journal of Hazardous Materials, 2026)

Immobilization mechanism of Ca(H2PO4)2-modified attapulgite on multiple heavy metals in mining soils: Speciation changes, risk assessment and ecotoxicity - Jun Ren; Rui Zhu; Hanru Ren; Ling Tao; Xuri Mu (Science of The Total Environment, 2026)

Melichumarin A, a new coumarin with nitric oxide inhibitory activity from the stems of Melicope chunii - Rui-Hong Zhu; Zi-Feng Liang; Zhong-Liu Zhou; Zi-Ming Chen; Qi Zhou; Jing-Ling Ren; Shou-Yuan Wu (Natural Product Research, 2025)

Bioactive sulfur-containing amides from the leaves of Glycosmis lucida - Shou-Yuan Wu; Hong-Yan Yang; Zhong-Liu Zhou; Zi-Feng Liang; Rui-Hong Zhu; Jing-Ling Ren; Pei-Lian Liu; Zi-Ming Chen (Natural Product Research, 2025)

Transcriptomic analysis of the mechanism of male reproductive injuries caused by the mixture of three phthalates in rats - Ling-Zi Xia; Jun-Zhe Yue; Li-Jun Wu; Qian-Ying Jin; Yi-Pei Yang; Jing-Yang Yu; Rui-Zhe Pan; Xin Zhang; Xiao-Ying Wu; Jiayin Zhu; Hai-Tao Gao (Toxicology and Applied Pharmacology, 2025)

Integrated enzymatic, transcriptomic, and metabolite identification insights into the degradation of diverse endocrine-disrupting compounds by Pleurotus ostreatus GEMB-PO1 - Yu Xun; Mingdong Zhu; Ling Feng; Nasi Zhang; Rui Zhuo (Journal of Hazardous Materials, 2025)

Remediation mechanism of KH2PO4 modified attapulgite on mining soil contaminated by heavy metals - Jun Ren; Xuri Mu; Hanru Ren; Ling Tao; Rui Zhu (Journal of Environmental Chemical Engineering, 2025)

Bioinspired conductive-catalytic network accelerates rate-determining steps at cathode-electrolyte interface for high-loading Li-S batteries - Cai-Yun Zhang; Chen-Yang Wang; En-Zhu Zhao; Guowei Yu; Hui-Ling Deng; Rui Huang; Zhao-Yun Wang; Pu Hu; Min Yan; Zhitian Liu (Chemical Engineering Journal, 2025)

Effect of human-driven hydrological change on vegetation distribution in the Shiyang River Basin - Yuhao Wang; Guofeng Zhu; Enwei Huang; Gaojia Meng; Jiawei Liu; Siyu Lu; Dongdong Qiu; Longhu Chen; Rui Li; Yinying Jiao; Ling Zhao; Xiaoyu Qi; et al. (Journal of Mountain Science, 2025)

Target analysis of per- and polyfluoroalkyl substances in surface water: Occurrence, seasonal trends, and risk-based prioritization in the Minjiang River - Hui Zhang; Xin-Yue Wang; Yu-Hua Zheng; Jing-Run Hu; Xiao-Lin Li; Hong-Ling Yin; Rui Xiao; Xiao-Lan Zhu; Ting Chen; Huan Chen (Science of The Total Environment, 2025)

Helicobacter pylori VacA-induced gastric mucosal atrophy: a comparative analysis with other forms of atrophic gastritis - Yang-Kun Wang; Wen-Rui Chen; Ling-Yan Lu; Ying-Ying Li; Rui-Kun Qiu; Chao-Ya Zhu; Fa-Shun Zhang; Su-Nan Wang; Si-Liang Xu (Journal of Molecular Histology, 2025)

Genome-based taxonomy of the family Haloarculaceae, proposal of Natronomonadaceae fam. nov., and description of four novel halophilic archaea from two saline lakes and a marine solar saltern - Ling-Rui Zhu; Ya-Ling Mao; Yao Hu; Ya-Ping Sun; Jing Hou; Heng-Lin Cui (Systematic and Applied Microbiology, 2025)

Development of potential intron polymorphic (PIP) markers in melon (Cucumis melo L.) - Rui Sun; Yan-Ge Li; Ding-Ding Zuo; Meng-Ling Zheng; Jing Zhang; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Genetic Resources and Crop Evolution, 2025)

Halobellus marinus sp. nov., Halobellus ordinarius sp. nov., Halobaculum rarum sp. nov., and Halorarum halobium sp. nov., halophilic archaea isolated from marine solar salt and a saline lake - Ling-Rui Zhu; Chidiebele Nwankwo; Jing Hou; Heng-Lin Cui (Extremophiles, 2025)

Mapping of leaf lobe-related genes in melon (Cucumis melo L.) via bulked segregant analysis - Meng-Ling Zheng; Lu Yang; Ding-Ding Zuo; Rui Sun; Jing Zhang; Yan-Ge Li; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Euphytica, 2025)

Groundwater environmental effects risk evaluation in mountain tunnel construction: A dynamic decision support system based on fuzzy two-dimensional cloud probability model - Huaiyuan Sun; Ling Le; Yiming Dai; Yi Rui; Hehua Zhu; Xiaojun Li; Xuhui Li; Guangwen Xue (Tunnelling and Underground Space Technology, 2025)

Development of chromosome-specific potential intron polymorphism markers in watermelon - Liang-Jie Li; Ding-Ding Zuo; Meng-Ling Zheng; Lu Yang; Rui Sun; Xue‑Jie Zhu; Zhong‑Hou Zhu; Da-Long Guo (Genetic Resources and Crop Evolution, 2025)

Surface-Enhanced Raman Scattering (SERS)-based biosensors for advanced extracellular vesicle detection: A review - Rui Fan; Siting Chen; Fei Lan; Wenbin Li; Yitong Zhu; Lifeng Zhang; Ye Zhang; Ling Li (Analytica Chimica Acta, 2025)

Assessing the climatic niche changes and global invasion risk of Solanum elaeagnifolium in relation to human activities - Xin-Di Li; Yu Chen; Chun-Ling Zhang; Jia Wang; Xing-Jiang Song; Xian-Rui Zhang; Zhi-Hong Zhu; Gang Liu (Science of The Total Environment, 2024)

Composition of four polyphenol fractions extracted from partridge tea and their mechanisms on ameliorate insulin resistance in HepG2 cells - Ke-Xin Hao; Ying-Jing Zhang; Rui-Fang Zhong; Yi-Meng Li; Ling Wang; Xiao Chang; Da-Wei Wang; Jian-Guo Jiang; Wei Zhu (Food Bioscience, 2024)

TP53 to mediate immune escape in tumor microenvironment: an overview of the research progress - Kai-li Zhu; Fei Su; Jing-ru Yang; Ruo-wen Xiao; Rui-yue Wu; Meng-yue Cao; Xiao-ling Ling; Tao Zhang (Molecular Biology Reports, 2024)
Increasing evidence suggests that key cancer-causing driver genes continue to exert a sustained influence on the tumor microenvironment (TME), highlighting the importance of immunotherapeutic targeting of gene mutations in governing tumor progression. TP53 is a prominent tumor suppressor that encodes the p53 protein, which controls the initiation and progression of different tumor types. Wild-type p53 maintains cell homeostasis and genomic instability through complex pathways, and mutant p53 (Mut p53) promotes tumor occurrence and development by regulating the TME. To date, it has been wildly considered that TP53 is able to mediate tumor immune escape. Herein, we summarized the relationship between TP53 gene and tumors, discussed the mechanism of Mut p53 mediated tumor immune escape, and summarized the progress of applying p53 protein in immunotherapy. This study will provide a basic basis for further exploration of therapeutic strategies targeting p53 protein.

Genome‑based classification of the family Natrialbaceae and description of four novel halophilic archaea from three saline lakes and a saline-alkaline land - Xin-Yue Dong; Ya-Ling Mao; Qing-Ke Zhang; Ling-Rui Zhu; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

Relative importance of altitude shifts with plant and microbial diversity to soil multifunctionality in grasslands of north-western China - Ning Wang; Junhui Cheng; Yunhua Liu; Qicheng Xu; Chen Zhu; Ning Ling; Junjie Guo; Rui Li; Wei Huang; Shiwei Guo; Baorong Wang; Shaoshan An; et al. (Plant and Soil, 2024)

Association of the COL4A2 Gene Polymorphisms with Primary Intracerebral Hemorrhage Risk and Outcome in Chinese Han Population - Huan Wang; Yuyi Zhu; Lukai Zheng; Mingxi Chen; Zilong Hao; Rui Guo; Ling Feng; Deren Wang (Molecular Neurobiology, 2024)

What is the spatiotemporal pattern of benzene concentration spread over susceptible area surrounding the Hartman Park community, Houston, Texas? - Aji Kusumaning Asri; Galen D. Newman; Zhihan Tao; Rui Zhu; Hsiu-Ling Chen; Shih-Chun Candice Lung; Chih-Da Wu (Journal of Hazardous Materials, 2024)

Methylene Blue Pretreatment Protects Against Repeated Neonatal Isoflurane Exposure-Induced Brain Injury and Memory Loss - Chongyun Wu; Qianting Deng; Ling Zhu; Timon Cheng-yi Liu; Rui Duan; Luodan Yang (Molecular Neurobiology, 2024)

Genome-based classification of the family Haloferacaceae and description of five novel species of Halobaculum - Shun Tan; Ling-Rui Zhu; Qing-Ke Zhang; Xin-Yue Dong; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

Development and characterization of a bacterial enzyme cascade reaction system for efficient and stable PET degradation - Chengyong Wang; Rui Long; Xiran Lin; Wei Liu; Liying Zhu; Ling Jiang (Journal of Hazardous Materials, 2024)

Two new steroids with cytotoxicities from fungus Acrocalymma cycadis - Li-Bin Lin; Deng-Gao Zhu; Ting Yang; Rui Han; Jia-Yao Hu; Wei Shi; Ze-Yi Li; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2024)

Dynamic surface-enhanced Raman spectroscopy and positively charged probes for rapid detection and accurate identification of fungal spores in infected apples via deep learning methods - Jinghong Wang; Rui Zhu; Yehang Wu; Le Tang; Cong Wang; Mengqing Qiu; Ling Zheng; Pan Li; Shizhuang Weng (Food Control, 2024)

Water Properties and Diffusive Convection in the Canada Basin - Ling Qu; Shuangxi Guo; Shengqi Zhou; Yuanzheng Lu; Mingquan Zhu; Xianrong Cen; Di Li; Wei Zhou; Tao Xu; Miao Sun; Rui Zeng (Journal of Marine Science and Engineering, 2024)
The aim of this study is to better understand diffusive convection (DC) and its role in the upper ocean dynamic environment and sea ice melting in the Canada Basin. Based on a moored dataset with 6737 profiles collected from August 2003 to August 2011 in the upper layer of the Canada Basin, DC between the warm and salty Atlantic Water (AW) and the colder and less salty Lower Halocline Water (LHW) were investigated. The moorings were designated at four stations: A, B, C, and D, located at the southwestern, southeastern, northeastern, and northwestern parts of the basin, respectively. During the observation period, the temperature, salinity, and depth of the AW and LHW exhibited unique temporal variations. The temperature and salinity of the AW varied among stations, with a decreasing trend from northwest to southeast, consistent with the propagation path of the AW in the Canada Basin. The temperature and salinity of the LHW were similar at all stations. The AW and LHW cores were located between depths of 320–500 m and 160–300 m, respectively, and both gradually deepened over time. Distinct DC staircase structures were observed between the AW and LHW, more pronounced at stations C and D than at stations A and B, which is speculated to be related to eddies at stations A and B during the observation period. The vertical heat fluxes through the DC staircase layer at stations C and D (FHc_C and FHc_D) were estimated using an empirical formula. FHc_C ranged from 0.05 to 0.94 W/m2, and FHc_D ranged from 0.05 to 0.6 W/m2, with the maximum probability value for both at approximately 0.2 W/m2. The effective diffusivities at these two stations (KT_C and KT_D) are similar, ranging from 2 × 10−6 to 3 × 10−5 m2/s, with the highest probability occurring at 6 × 10−6 m2/s. Both the probability density function of the heat flux and the effective diffusivity skewed towards larger values and obey a lognormal distribution, indicating turbulence intermittency of the DC staircase in the Canada Basin. These finding offers new insights into the heat transport and turbulence in the DC staircase, and then bring a deeper understanding of sea ice melting in the Canada Basin.

AM fungus promotes wheat grain filling via improving rhizospheric water & nutrient availability under drought and low density - Hai-Xia Duan; Chong-Liang Luo; Rui Zhou; Ling Zhao; Shuang-Guo Zhu; Yinglong Chen; Ying Zhu; You-Cai Xiong (Applied Soil Ecology, 2024)

Early clues and molecular mechanism involved in neurodegenerative diseases induced in immature mice by combined exposure to polypropylene microplastics and DEHP - Ge Yang; Cunyi Gong; Xinyue Zheng; Fei Hu; Jie Liu; Tian Wang; Xinyue Chen; Min Li; Zhihong Zhu; Ling Zhang; Rui Li (Environmental Pollution, 2023)

Space charge region induced self-evolution dehydrogenation of polymorphic magnesium-based hydrides - Qinke Tang; Jiangchuan Liu; Mengran Li; Rui Shi; Yunfeng Zhu; Yao Zhang; Jiguang Zhang; Yana Liu; Yijin Wu; Ling Li; Xiaohui Hu; Liquan Li (Chemical Engineering Journal, 2023)

Ru-catalyzed chemoselective methoxycarbonylation of methyl pentenoate: An assistant role of chloride anions - Shu Zhang; Rui Sun; Pengxin Guan; Yaofeng Wang; Ling Wang; Yanli Zhu; Lijun Han; Jiayu Xin (Chemical Engineering Journal, 2023)

Construction of S-scheme Zn0.2Cd0.8S/biochar aerogel architectures for boosting photocatalytic hydrogen production under sunlight irradiation - Chonghai Deng; Lulu Peng; Xiaohui Ling; Tao Wang; Rui Xu; Yibin Zhu; Chenchen Wang; Xuehui Qian; Lili Wang; Yiping Wu; Hanmei Hu; Yongsheng Han (Journal of Cleaner Production, 2023)

Estimation of urban-scale photovoltaic potential: A deep learning-based approach for constructing three-dimensional building models from optical remote sensing imagery - Longxu Yan; Rui Zhu; Mei-Po Kwan; Wei Luo; De Wang; Shangwu Zhang; Man Sing Wong; Linlin You; Bisheng Yang; Biyu Chen; Ling Feng (Sustainable Cities and Society, 2023)

Molecular Hydrogen: an Emerging Therapeutic Medical Gas for Brain Disorders - Chongyun Wu; Peibin Zou; Shu Feng; Ling Zhu; Fanghui Li; Timon Cheng-Yi Liu; Rui Duan; Luodan Yang (Molecular Neurobiology, 2023)

Changes in the Microbiota and their Roles in Patients with Type 2 Diabetes Mellitus - Qiao-ling He; Hui-chao Wang; Yu-ke Ma; Rui-lin Yang; Zhi-feng Dai; Jing-nan Yang; Yao Xu; Dan-dan Wei; Li-ping Zhu; Xu-hong Lin (Current Microbiology, 2023)

Evaluation of a GNSS for wave measurement and directional wave spectrum analysis - Hanbin Gu; Xiaoan Zhu; Rui Shan; Jun Zang; Ling Qian; Pengzhi Lin (Ocean Engineering, 2023)

Lanthanoid hydrogen-bonded organic frameworks: Enhancement of luminescence by the coordination-promoted antenna effect and applications in heavy-metal ion sensing and sterilization - Yun-Lan Li; Hai-Ling Wang; Zhi-Chuan Chen; Zhong-Hong Zhu; Yan-Cheng Liu; Rui-Yun Yang; Fu-Pei Liang; Hua-Hong Zou (Chemical Engineering Journal, 2023)

RIG-I acts as a tumor suppressor in melanoma via regulating the activation of the MKK/p38MAPK signaling pathway - Rui Guo; Shun-Yuan Lu; Jin-Xia Ma; Qian-Lan Wang; Lu Zhang; Ling-Yun Tang; Yan Shen; Chun-Ling Shen; Jin-Jin Wang; Li-Ming Lu; Zhu-Gang Wang; Hong-Xin Zhang (Human Cell, 2022)
Studies have indicated that RIG-I may act as a tumor suppressor and participate in the tumorigenesis of some malignant diseases. However, RIG-I induces distinct cellular responses via different downstream signaling pathways depending on the cell type. To investigate the biological function and underlying molecular mechanism of RIG-I in the tumorigenesis of melanoma, we constructed RIG-I knockout, RIG-I -overexpressing B16-F10 and RIG-I knockdown A375 melanoma cell lines, and analyzed the RIG-I-mediated change in the biological behavior of tumor cells in spontaneous and poly (I:C)-induced RIG-I activation. Cell proliferation, cell cycling, apoptosis and migration were detected by CCK-8 assay, BrdU incorporation assay, Annexin V–PI staining assay and Transwell assay, respectively. In vivo tumorigenicity was evaluated by tumor xenograft growth in nude mice and subsequently by Ki67 staining and TUNEL assays. Furthermore, Western blotting was utilized to explore the underlying mechanism of RIG-I in melanoma cells. Our data showed that RIG-I promotes apoptosis and inhibits proliferation by G1 phase cell cycle arrest in the melanoma cell lines. Mechanistically, RIG-I induced the phosphorylation of p38 MAPK and MAPK kinases MKK3 and MKK4. In conclusion, the current study demonstrated that RIG-I suppressed the development of melanoma by regulating the activity of the MKK/p38 MAPK signaling pathway, which is relevant to research on novel therapeutic targets for this malignant disease.

Narrative Cartography with Knowledge Graphs - Gengchen Mai; Weiming Huang; Ling Cai; Rui Zhu; Ni Lao (Journal of Geovisualization and Spatial Analysis, 2022)
Narrative cartography is a discipline which studies the interwoven nature of stories and maps. However, conventional geovisualization techniques of narratives often encounter several prominent challenges, including the data acquisition & integration challenge and the semantic challenge. To tackle these challenges, in this paper, we propose the idea of narrative cartography with knowledge graphs (KGs). Firstly, to tackle the data acquisition & integration challenge, we develop a set of KG-based GeoEnrichment toolboxes to allow users to search and retrieve relevant data from integrated cross-domain knowledge graphs for narrative mapping from within a GISystem. With the help of this tool, the retrieved data from KGs are directly materialized in a GIS format which is ready for spatial analysis and mapping. Two use cases — Magellan’s expedition and World War II — are presented to show the effectiveness of this approach. In the meantime, several limitations are identified from this approach, such as data incompleteness, semantic incompatibility, and the semantic challenge in geovisualization. For the later two limitations, we propose a modular ontology for narrative cartography, which formalizes both the map content ( Map Content Module) and the geovisualization process ( Cartography Module). We demonstrate that, by representing both the map content and the geovisualization process in KGs (an ontology), we can realize both data reusability and map reproducibility for narrative cartography.

A feasible vibration measurement and active control method of reinforced concrete lightweight pier railway bridges for heavy-haul monorail trains - Ling-kun Chen; Li-zhong Jiang; Rui Li; Qiao Li; Ming Zhang; Nan Zhang; Jin-zhang Luo; Liang Ling; Sheng-yang Zhu (European Journal of Environmental and Civil Engineering, 2022)

On the Mechanism of High-Voltage Pulsed Fragmentation from Electrical Breakdown Process - Xiaohua Zhu; Yunxu Luo; Weiji Liu; Ling He; Rui Gao; Yudan Jia (Rock Mechanics and Rock Engineering, 2021)

Rescue effects of Se-enriched rice on physiological and biochemical characteristics in cadmium poisoning mice - Yang Su; Ling Li; Muhammad Umer Farooq; Xin Huang; Tengda Zheng; Yu Jie Zhang; Hla Hla Ei; Faiz Hussain Panhwar; Zhichen Tang; Rui Zeng; Yuanke Liang; Xiaoying Ye; et al. (Environmental Science and Pollution Research, 2021)

Association Between Blood Heavy Metal Concentrations and Dyslipidemia in the Elderly - Xingmeng Zhu; Yong Fan; Jie Sheng; Ling Gu; Qi Tao; Rui Huang; Kaiyong Liu; Linsheng Yang; Guimei Chen; Hongjuan Cao; Kaichun Li; Fangbiao Tao; et al. (Biological Trace Element Research, 2021)

Arbuscular mycorrhizal colonization rate of an exotic plant, Galinsoga quadriradiata, in mountain ranges changes with altitude - Gang Liu; Rui-Ling Liu; Wen-Gang Zhang; Ying-Bo Yang; Xiao-Qiong Bi; Ming-Zhu Li; Xiao-Yan Chen; Hua Nie; Zhi-Hong Zhu (Mycorrhiza, 2021)

Mapping landslide susceptibility at the Three Gorges Reservoir, China, using gradient boosting decision tree, random forest and information value models - Tao Chen; Li Zhu; Rui-qing Niu; C John Trinder; Ling Peng; Tao Lei (Journal of Mountain Science, 2020)

Response of organic carbon fractions and microbial community composition of soil aggregates to long-term fertilizations in an intensive greenhouse system - Lihong Tong; Ling Zhu; Yizhong Lv; Kun Zhu; Xiayan Liu; Rui Zhao (Journal of Soils and Sediments, 2020)

Overexpression of AtAGT1 promoted root growth and development during seedling establishment - Rui Wang; Lin Yang; Xiaofang Han; Yuhong Zhao; Ling Zhao; Beibei Xiang; Yerong Zhu; Yanling Bai; Yong Wang (Plant Cell Reports, 2019)

Diversification of mitogenomes in three sympatric Altica flea beetles (Insecta, Chrysomelidae) - Rui‐E Nie; Jing Wei; Shou‐Ke Zhang; Alfried P. Vogler; Ling Wu; Alexander S. Konstantinov; Wen‐Zhu Li; Xing‐Ke Yang; Huai‐Jun Xue (Zoologica Scripta, 2019)
The Asian flea beetles Altica cirsicola , Altica fragariae and Altica viridicyanea are broadly sympatric and morphologically highly similar but feed on distantly related host plants. They have been suggested as a model for ecological speciation studies. However, their phylogeny and species limits remain uncertain. In this study, we added mitochondrial genomes from multiple individuals of each species to the growing database. Phylogenetic analyses based on 15 genes showed clear interspecific divergences of A. fragariae from the other species, but A. cirsicola and A. viridicyanea were not distinguishable by distance‐based or tree‐based methods of species delimitation due to non‐monophyly of mitogenomes relative to the morphologically defined entities, possibly affected by interspecific introgression. This was confirmed by wider sampling of mitochondrial COX1 (58 individuals) and the second internal transcribed spacer of nuclear ribosomal RNA cluster (ITS2; 68 individuals), which showed that ITS2, but not COX1, coincided with the morphological species limits. The full mitochondrial genomes are not able to shed further light on the species status, even with the most sensitive approach based on diagnostic characters, yet the whole mitogenome is useful to get improved estimates of intra‐ and interspecific variation, not affected by the stochastic error seen in individual genes.

Long noncoding RNA UCA1 promotes the proliferation of hypoxic human pulmonary artery smooth muscle cells - Tian-Tian Zhu; Rui-Li Sun; Ya-Ling Yin; Jin-Ping Quan; Ping Song; Jian Xu; Ming-Xiang Zhang; Peng Li (Pflügers Archiv - European Journal of Physiology, 2019)

Acupuncture Prevents the Impairment of Hippocampal LTP Through β1-AR in Vascular Dementia Rats - Ling-Yong Xiao; Xue-Rui Wang; Jing-Wen Yang; Yang Ye; Wen Zhu; Yan Cao; Si-Ming Ma; Cun-Zhi Liu (Molecular Neurobiology, 2018)

The N-terminal and central domain of colicin A enables phage lysin to lyse Escherichia coli extracellularly - Guangmou Yan; Jianfang Liu; Qiang Ma; Rining Zhu; Zhimin Guo; Chencheng Gao; Shuang Wang; Ling Yu; Jingmin Gu; Dongliang Hu; Wenyu Han; Rui Du; et al. (Antonie van Leeuwenhoek, 2017)

Correlation of rs9331888 polymorphism with Alzheimer’s disease among Caucasian and Chinese populations: a meta-analysis and systematic review - Bin Zhu; Rui Min Wang; Jian Ting Wang; Rui Ling Chen; Yan Fei Zheng; Lei Zhang; Zhi Gang Zhao (Metabolic Brain Disease, 2017)

Molecular Mechanisms of Vascular Dementia: What Can Be Learned from Animal Models of Chronic Cerebral Hypoperfusion? - Si-Qi Du; Xue-Rui Wang; Ling-Yong Xiao; Jian-Feng Tu; Wen Zhu; Tian He; Cun-Zhi Liu (Molecular Neurobiology, 2017)

Estimation of Permeability from NMR Logs Based on Formation Classification Method in Tight Gas Sands - Deng-Feng Wei; Xiao-Peng Liu; Xiao-Xin Hu; Rui Xu; Ling-Ling Zhu (Acta Geophysica, 2015)

DNA methylation level of promoter region of activating transcription factor 5 in glioma - Xiao-min Hua; Juan Wang; Dong-meng Qian; Jing-yi Song; Hao Chen; Xiu-li Zhu; Rui Zhou; Yu-dan Zhao; Xiu-zhi Zhou; Ling Li; Li Zhang; Xu-xia Song; et al. (Journal of Zhejiang University-SCIENCE B, 2015)

Characterization of 15 polymorphic microsatellite loci for the jellyfish Rhopilema esculentum - Ling Zhu; Ao-ao Yang; Chun-ya Zhou; Hong Yang; Xiao-rui Luo; Si-Qing Chen; Zhi-meng Zhuang (Conservation Genetics Resources, 2015)

Historical development and future perspectives of Environmental Specimen Bank in China: a mini review - Fang Qiu; Xiang-Zhou Meng; Yan-Ling Qiu; Qing-Hui Huang; Ying Liu; Ling-Ling Wu; Qian-Fen Xiao; Ya-Jie Sun; Rui Wang; Yi-Hui Zhou; Zhen-Yang Yu; Da-Qiang Yin; et al. (Environmental Science and Pollution Research, 2015)

Upregulation of HIF-1α Via Activation of ERK and PI3K Pathway Mediated Protective Response to Microwave-Induced Mitochondrial Injury in Neuron-Like Cells - Li Zhao; Yue-Feng Yang; Ya-Bing Gao; Shui-Ming Wang; Li-Feng Wang; Hong-Yan Zuo; Ji Dong; Xin-Ping Xu; Zhen-Tao Su; Hong-Mei Zhou; Ling-Ling Zhu; Rui-Yun Peng (Molecular Neurobiology, 2014)

Involvement of calcium-sensing receptors in hypoxia-induced vascular remodeling and pulmonary hypertension by promoting phenotypic modulation of small pulmonary arteries - Xue Peng; Hong-Xia Li; Hong-Jiang Shao; Guang-Wei Li; Jian Sun; Yu-Hui Xi; Hong-Zhu Li; Xin-Yan Wang; Li-Na Wang; Shu-Zhi Bai; Wei-Hua Zhang; Li Zhang; et al. (Molecular and Cellular Biochemistry, 2014)

Lack of association between the polymorphisms of hypoxia-inducible factor 1A (HIF1A) gene and SLE susceptibility in a Chinese population - Chen-Chen Feng; Qian-Ling Ye; Yan Zhu; Rui-Xue Leng; Gui-Mei Chen; Jie Yang; Han Cen; Xiao-Ke Yang; Rui Li; Wang-Dong Xu; Hai-Feng Pan; Dong-Qing Ye (Immunogenetics, 2014)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Quaternary palaeoenvironmental oscillations drove the evolution of the Eurasian Carassius auratus complex (Cypriniformes, Cyprinidae) - Yun Gao; Shu‐Yan Wang; Jing Luo; Robert W. Murphy; Rui Du; Shi‐Fang Wu; Chun‐Ling Zhu; Yan Li; Andrei D. Poyarkov; Sang Ngoc Nguyen; Peng‐Tao Luan; Ya‐Ping Zhang (Journal of Biogeography, 2012)
Aim We sought to reconstruct the spatio‐temporal genetic diversification in goldfish of the Carassius auratus complex, which is widely distributed in Eurasia, to test whether vicariance events or human‐mediated translocations best explained lineage divergence and genogeographical history. Location East Asia and the Oriental islands including Japan, the Ryukyus and Taiwan, and Europe, including Russia and the Czech Republic. Methods We reconstructed the matrilineal history of Eurasian goldfish using 1876 sequences from the partial mitochondrial DNA control region (426 bp) and 191 complete sequences of cytochrome b (1140 bp) from 67 localities representing most of the range of the species. Divergence times were estimated using a Bayesian Markov chain Monte Carlo approach based either on molecular clock data or on the fossil record. Genetic structure and the historical demography of populations were analysed using partial correlation tests and analyses of molecular variance. Results Three lineages had high levels of regional specificity. Lineages A and B from the main islands of Japan differed greatly from lineage C, which occurred on the mainland, Taiwan and the Ryukyus. Lineages A and B had late Pliocene origins. Six geographically constrained sublineages within lineage C had near‐simultaneous mid‐Pleistocene divergences. Main conclusions Genetic structure in the C. auratus complex appears to have been driven by palaeoenvironmental perturbations rather than human translocations. The disappearance of a land bridge in the Tsushima Strait around 3.0 Ma is responsible for the separation of Japanese and continental lineages; the estimated divergence time is 2.75–2.32 Ma. Fujian, China and Vietnam appear to have provided important refugia for the C. auratus complex during glaciation. After warm, moist summer monsoons intensified during the mid‐Pleistocene, goldfish are likely to have dispersed north‐eastwards to recolonize the Ryukyus via Taiwan and northwards to recolonize mainland China.

Molecular characterization and phylogenetic analysis of porcine epidemic diarrhea virus (PEDV) field strains in south China - Zhi-Li Li; Ling Zhu; Jing-Yun Ma; Qing-Feng Zhou; Yan-Hua Song; Bao-Li Sun; Rui-Ai Chen; Qing-Mei Xie; Ying-Zuo Bee (Virus Genes, 2012)

Involvement of calcium-sensing receptor in oxLDL-induced MMP-2 production in vascular smooth muscle cells via PI3K/Akt pathway - Hong-Xia Li; Fan-Juan Kong; Shu-Zhi Bai; Wen He; Wen-Jing Xing; Yu-Hui Xi; Guang-Wei Li; Jin Guo; Hong-Zhu Li; Ling-Yun Wu; Rui Wang; Guang-Dong Yang; et al. (Molecular and Cellular Biochemistry, 2012)

The functional expression of calcium-sensing receptor in the differentiated THP-1 cells - Yu-hui Xi; Hong-zhu Li; Wei-hua Zhang; Li-na Wang; Li Zhang; Yan Lin; Shu-zhi Bai; Hong-xia Li; Ling-yun Wu; Rui Wang; Chang-qing Xu (Molecular and Cellular Biochemistry, 2010)

Research development of the pathogenesis pathways for neuroschistosomiasis - Peng Wang; Ming-Can Wu; Shi-Jie Chen; Guo-Cai Luo; Xiang-Ling Cheng; Zhan-Sheng Zhu; Guang-Rui Zhao (Neuroscience Bulletin, 2010)